Spatial magnitude-frequency index of mass movements in the humid tropics - Colangelo, Antonio C.; Cruz, Olga (GEOUSP Espaço e Tempo (Online), 2000)
The Ahnert's (1987) sem ilogarithm ic approach was adapted and applied directly in slump units deposits and scars m apped in airphotos. In this case, the magnitude-frequency index refers to the "Sp atial Recurrence Interval" (SRI: in Km 2 ) or "Spatial Frequency" (SF: in Events / Km 2) of deposits and scars of varying magnitudes (Dep or DSc in: m2). For migmatite parent m aterial area with steeps slops, the equation results: Dep (m 2) = 4558.Ln(SRI) + 10315. For tertiary parent m aterial area with smooth relief, m oderate gradients, the equation results: Dep (m 2) = 1 5 132.Ln(SRI) + 19106. The "dom inant mass movem ent event" is the event with the m ajor product of magnitude for freqüêncy and that contribute with the bigger total amount of surface affected: deposits and scars. In the two areas referred above the dom inant events have deposits sufaces with, respectively: 4558m 2 and 15132m2. In the sam e way, the spatial frequency of ocurrence are respectively: 3,54 Events/Km 2 (SRI = 0,282 Km 2) and 1,30 Events/Km 2 (SRI = 0,769 Km 2). Under the light of these prelim inary results it seem s to there is a com pensation m echanism related to a possible clim atic constant that constrain the behavior of spatial m agnitude-frequency of this kind of events in the humid tropics